MERANCANG MANAJEMEN AGRIBISNIS SYARIAH DI DESA CINANGNENG, KECAMATAN TENJOLAYA, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Muhammad Alvin Ridallah (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
This community service aims to design a sharia agribusiness management in Cingneng Village, Tenjolaya District, Bogor Regency, West Java Province. In this community service activity, activities are carried out based on participatory methods which involve the community with various suggestions and opinions as well as aspects of life that surround the people in the village. Counseling and consolidation activities were also carried out so that agriculture in the village developed. With this community service, it can be concluded that the development of agribusiness, especially in the development of agro-industry, can be directed not only to increase the achievement of economic efficiency, but also to increase equity and justice.